Contribuição ao conhecimento das Aspidosperma da Amazônia Brasileira (Apocynaceae). Aspidosperma carapanauba Pichon, A. mascgravianum Woodson e A. oblongum A. DC. - Albuquerque, Byron Wilson (Acta Amazonica, 1971)
This paper is a contribution to the knowledge of the Aspidosperma of Brazilian Amazonia. Morphology of petiole and leaf-blade are studied. Flowers, fruits and geographical distribution are also considered. Foliar morphology may be used for specific identification. Tables I and II present characters common and peculiar to each species. Results are documented by drawings.